2020
DOI: 10.1101/2020.06.04.134718
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Akt is required for artery formation during embryonic vascular development

Abstract: One of the first events in the development of the cardiovascular system is morphogenesis of the main embryonic artery, the dorsal aorta (DA). The DA forms via a conserved genetic process mediated by the migration, specification, and organization of endothelial progenitor cells into a distinct arterial lineage and vessel type. Several angiogenic factors activate different signaling pathways to control DA formation, however the physiological relevance of distinct kinases in this complex process remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…Although the role of foxo1a and foxo1b in zebrafish vasculature has been little studied, a recent study has reported that foxo1 is involved in embryonic vascular development [57]. Investigations have revealed that the depletion of foxo1, specifically in endothelial cells, enhances metabolic activity and promotes angiogenesis in both normal and obese mice, thus indicating its inhibitory role in angiogenesis, which aligns with our own findings.…”
Section: Discussionsupporting
confidence: 89%
“…Although the role of foxo1a and foxo1b in zebrafish vasculature has been little studied, a recent study has reported that foxo1 is involved in embryonic vascular development [57]. Investigations have revealed that the depletion of foxo1, specifically in endothelial cells, enhances metabolic activity and promotes angiogenesis in both normal and obese mice, thus indicating its inhibitory role in angiogenesis, which aligns with our own findings.…”
Section: Discussionsupporting
confidence: 89%